Quantification of Enzymatic Biofilm Removal Using the Sauerbrey Equation: Application to the Case of Pseudomonas protegens - Levy, Ivana Karina (2024)
A methodology for the quantitative analysis of enzymatic removal of biofilms (BF) was developed, based on a quartz crystal microbalance (QCM) under stationary conditions. This was applied to the case of Pseudomonas protegens (PP) BFs, through a series of five enzymes, whose removal activity was screened using the presented methodology. The procedure is based on the following: when BFs can be modeled as rigid materials, QCM can be used as a balance under stationary conditions for determining the BFs mass reduction by enzymatic removal. For considering a BF as a rigid model, energy dissipation effects, associated with viscoelastic properties of the BF, must be negligible. Hence, a QCM system with detection of dissipation (referred to as QCM with dissipation) was used for evaluating the energy losses, which, in fact, resulted in negligible energy losses in the case of dehydrated PP BFs, validating the application of the Sauerbrey equation for the change of mass calculations. The stationary methodology reduces operating times and simplifies data analysis in comparison to dynamic approaches based on flow setups, which requires the incorporation of dissipation effects due to the liquid media. By carrying out QCM, glycosidase-type enzymes showed BF removal higher than 80% at enzyme concentration 50 ppm, reaching removal over 90% in the cases of amylase and cellulase/xylanase enzymes. The highest removal percentage produced a reduction from about 15 to 1 μg in the BF mass. Amylase enzyme was tested from below 50 to 1 ppm, reaching around 60% of removal at 1 ppm. The obtained results were supported by other instrumental techniques such as Raman spectroscopy, attenuated total reflection Fourier transform infrared spectroscopy, atomic force microscopy, high performance anion exchange chromatography, thermogravimetric analysis, and differential scanning calorimetry. The removal quantifications obtained with QCM were compared with those obtained by well-established screening techniques (UV–vis spectrophotometry using crystal violet and agar diffusion test). The proposed methodology expands the possibility of using a quartz microbalance to perform enzymatic activity screening.